Determinants of folic acid supplement use outside national recommendations for pregnant women: results from the Growing Up in New Zealand cohort study. Issue 12 (30th April 2018) - Teixeira, Juliana A; Castro, Teresa G; Wall, Clare R; Marchioni, Dirce Maria; Berry, Sarah; Morton, Susan MB; Grant, Cameron C
Abstract: Objective: To evaluate the sociodemographic and lifestyle factors associated with insufficient and excessive use of folic acid supplements (FAS) among pregnant women. Design: A pregnancy cohort to which multinomial logistic regression models were applied to identify factors associated with duration and dose of FAS use. Setting: The Growing Up in New Zealand child study, which enrolled pregnant women whose children were born in 2009–2010. Subjects: Pregnant women ( n 6822) enrolled into a nationally generalizable cohort. Results: Ninety-two per cent of pregnant women were not taking FAS according to the national recommendation (4 weeks before until 12 weeks after conception), with 69 % taking insufficient FAS and 57 % extending FAS use past 13 weeks' gestation. The factors associated with extended use differed from those associated with insufficient use. Consistent with published literature, the relative risks of insufficient use were increased for younger women, those with less education, of non-European ethnicities, unemployed, who smoked cigarettes, whose pregnancy was unplanned or who had older children, or were living in more deprived households. In contrast, the relative risks of extended use were increased for women of higher socio-economic status or for whom this was their first pregnancy and decreased for women of Pacific v. European ethnicity. Conclusions: In New Zealand, current use of FAS during pregnancy potentially exposes pregnant women and their unborn children to too little or too much folic acid. Further policy development is necessary to reduce current socio-economic inequities in the use of FAS.